-sqrt2, 6sqrt2?

using principle of zero products, write an equation

2 Answers

  • Best Answer

    well it seems that these are zeros of a polynomial, roots of a quadratic equation. We know that radical roots come in pairs. so we also have sqrt(2) and -sqrt(2)

    then we can write our factors:

    (x -sqrt(2))(x+sqrt(2))(x-6sqrt(2))(x+6sqrt(2)) =

    (x^2 -2)(x^2 - 72) =

    x^4 -72x^2 -2x^2 + 144 =

    x^4 -74x^2 +144

  • 1 decade ago

    Strange wording: I've not heard the expression "principle of zero products" before. Does it mean, a quadratic equation with these as roots?

    If so,

    (x + √2).(x - 6√2) = 0

    x² - 5√2.x -12 = 0

Still have questions? Get your answers by asking now.